Environmental, Social, Governance (ESG) Disclosure, Return on Equity, and Company Value: Evidence from Non-Financial Companies in Indonesia (International Forum of Researchers and Lecturers, 2024)
This study aims to analyze the impact of environmental, social, and governance disclosure, as well as return on equity, on company value. 364 non-financial companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2022 comprise the study's population. The purposive sampling, the chosen sampling technique, yielded 116 companies and a total of 464 observations. The study used secondary data, specifically financial statements and annual reports, along with documentary techniques to gather research data. The study employed panel data analysis and hypothesis testing, utilizing the EViews version 12 application. The results indicated that there was no significant impact of environmental, social, governance, and return on equity on the company value.